2016
DOI: 10.1111/scd.12213
|View full text |Cite
|
Sign up to set email alerts
|

Dental caries and associated factors in twins with Down syndrome: a case report

Abstract: Down syndrome (DS) is the most common genetic disorder in humans, but its incidence in monozygotic twins is extremely rare. The aim of this study was to determine the factors associated with dental caries in a pair of monozygotic twin girls with DS, where one had caries experience and the other did not. Clinical examination, salivary Streptococcus mutans (S. mutans) levels and their genotypic diversity, the biochemical composition of the dental biofilm, the frequency of sucrose consumption, and toothbrushing h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…The author concluded that environmental influence was dominant in caries initiation, whereas heredity was of little influence. 28–31 Lundstrom while summarizing a number of investigations of these types concluded that about 40% of the dental and facial variations can be attributed to hereditary factors. 32…”
Section: Discussionmentioning
confidence: 99%
“…The author concluded that environmental influence was dominant in caries initiation, whereas heredity was of little influence. 28–31 Lundstrom while summarizing a number of investigations of these types concluded that about 40% of the dental and facial variations can be attributed to hereditary factors. 32…”
Section: Discussionmentioning
confidence: 99%